Testing the Margins of Leisure Case Studies on China, Japan, and Indonesia - Wagner, Rudolf G.; Yeh, Catherine V.; Menegon, Eugenio; Weller, Robert P. (Heidelberg Studies on Transculturality, 2020)
This volume offers eight studies on different historical and present-day aspects of leisure in Asia. It critically engages with the predominant Eurocentric focus of leisure studies, bringing into the discussion a number of crucial issues such as the role of leisure as a transcultural contact zone. The volume engages with a field that has been rapidly growing due to the heightened role of leisure activities in defining a person's identity, the fading of the work/leisure divide in the post-industrial age, and the increasing economic importance of leisure pursuits such as tourism. Bringing Asia into the discussion contributes in resetting the study of leisure into a truly global context. Abstract in other languages